Distance Advanced Training of Preschool Teachers in Ukraine: Quantitative Indicators - Tetiana Sharova; Volodymyr Voronov; Sergii Sharov; Halyna Kolomoiets; Anna Voronova (CV FOUNDAE, 2024)
This study examines the stages involved in organizing distance learning advanced training courses and provides a quantitative analysis of preschool educators participating in the